Formation of Low-Valent Metal Templates Using Simple Amino Acids - SINGH, T.K.; KUMAR, ASHOK (Asian Journal of Chemistry, 2010)
Low-valent metal templates of the general formula [HL]2-M2L' (HL = glycine and alanine; M = univalent metal (Li, Na and K); L' = deprotonated acid resorcino ).have been constructed using glycine and alanine in non-aqueous solvent. The use of this work is to remove univalent metals from their complexes with the help of stem bark of some cultivars of mango containing these free amino acids such as glycine and alanine.